ADOPSI GOOD AGRICULTURAL PRACTICE (GAP) JAGUNG HIBRIDA UNTUK MENINGKATKAN PRODUKTIVITAS JAGUNG OLEH PETANI - Suprihatin Suhana; Asda Rauf; Zulham Sirajuddin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2023)
One of the reasons for the low productivity of corn is the low adoption of technology in corn cultivation. The objectives of this study were to: (1) determine the innovation components of GAP in hybrid corn cultivation, (2) identify the diversity of adoption of technology components in GAP of corn carried out by farmers, and (3) identify the characteristics of farmers that correlate with the adoption of GAP in hybrid corn. The method used in this study is a combination of qualitative and quantitative methods (mixed method), with a sequential exploratory model design. This research was conducted in Pilolaheya Village, Bone Bolango Regency, Gorontalo Province, with 60 corn farmers as respondents. The results showed that there were ten components in GAP corn cultivation that could increase maize productivity by farmers in Pilolaheya Village. Among these components, harvesting on time, drying immediately after harvest, and pests and diseases control in corn plants are the components with the highest adoption rate, and the components of planting one seed per one hole, using organic fertilizer, and piling up corn roots are components with the lowest adoption rate. The characteristic that correlates with farmer adoption is the level of education, where farmers who attained a higher level of education tend to adopt the innovation component in the GAP of corn cultivation.